High-dose ranibizumab therapy for vascularized pigment epithelial detachment - Chan, C K (Nature Publishing Group, 2012)
PURPOSE: The conventional dose of anti-vascular endothelial growth factor treatment may slowly reduce the subretinal fluid and height of a vascularized pigment epithelial detachment (vPED), but rarely leads to its complete resolution. We report a dramatic outcome involving a high dose (2 mg) of ranibizumab for treating vPED. METHODS: This report describes three eyes with vPED that received 2 mg in 0.05 ml of ranibizumab injections on a monthly basis and were followed prospectively. Each patient received a complete ocular examination, including best-corrected standardized ETDRS testing, fundus photography (FP), fluorescein angiography (FA), optical coherent tomography (OCT), and indocyanine-green angiography at baseline. ETDRS and OCT testing were repeated monthly, while FP and FA were performed every 3 months. RESULTS: Following a single intravitreal injection of 2 mg ranibizumab, there was rapid resolution of the subretinal fluid, haemorrhage, exudates, and flattening of the vPED within 10 days for Case 1, and within 1 month for Case 2 and Case 3. CONCLUSION: Rapid and dramatic decrease in the exudative changes and collapse of the vPED may develop after a single injection of high-dose (2 mg) ranibizumab in certain eyes with a vPED. The improvement was maintained with additional monthly injections to 12 months.